Análise do comportamento mecânico de vigotes de concreto armado em situação de incêndio, submetidos a níveis de carregamento proporcionais ao estado limite de serviço (ELS) para fissuração - Gross, Lucas Henrique Alves da Rosa (2024)
In modern times, it is evident that concrete is a widely used construction material worldwide, a characteristic attributed to its versatility, as well as its positive characteristics when analyzed from the perspective of its properties in both its fresh and hardened states. Concrete is also composed of elements that are abundantly available in nature and has a low economic cost compared to other construction materials. Concrete performs well under high temperatures compared to other commonly used construction materials, due to its incombustibility, low thermal conductivity, and lack of toxic gas emissions. Nonetheless, due to its strictly heterogeneous composition, increased temperature leads to mechanical, physical, and chemical transformations in each of its constituent materials, which can, under certain conditions, compromise its structural integrity. This research evaluates the effects on concrete when subjected to temperatures developed in compartment fires in buildings (obtained through the experimental application of a real fire simulator) during the exposure time necessary for the complete development and decay of the fire, considering the parametrization of the real fire development curve over time. For the analysis, flexural strength tests were conducted on reinforced concrete beams exposed to the compartment fire developed by the flashover simulator. These beams were also subjected to flexural loading proportional to the Service Limit State (SLS) for cracking, to analyze the effects of the degree of cracking on the loss of concrete properties. The results indicate that exposure to fire caused a loss of flexural strength in the beams, with a 32% reduction in non-preloaded specimens. Increased preloading, close to the SLS, reduced the residual strength, with significant differences between specimens tested at room temperature and those exposed to heat. In the group that exceeded the SLS, there was an 86% reduction in strength after the fire. This indicates that structural elements with loads above the SLS may maintain stability at room temperature but lose strength when exposed to heat. In the REF – INC, 50% - INC, and 100% - AMB groups, there were no significant differences, indicating that fire in stable structures can cause cracking beyond the acceptable level. The cracking, worsened before and after the fire, highlights the importance of considering the impact of heat on the integrity of concrete.